2019
DOI: 10.1038/s41598-019-40895-x
|View full text |Cite
|
Sign up to set email alerts
|

Sizing biological cells using a microfluidic acoustic flow cytometer

Abstract: We describe a new technique that combines ultrasound and microfluidics to rapidly size and count cells in a high-throughput and label-free fashion. Using 3D hydrodynamic flow focusing, cells are streamed single file through an ultrasound beam where ultrasound scattering events from each individual cell are acquired. The ultrasound operates at a center frequency of 375 MHz with a wavelength of 4 μm; when the ultrasound wavelength is similar to the size of a scatterer, the power spectra of the backscattered ultr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…We have previously demonstrated that waveforms of US signals backscattered from individual biological cells are unaffected by cell nuclei since they are acoustically homogeneous at UHFs. 34 Indeed, the presence of a strongly scattering object within the cell would result in either one or two additional peaks in the time-domain signal depending on the size of the nucleus; however, such peaks were not observed in our experiments. While the US measurements are unaffected by the presence of the cell nucleus, the PA measurements are insensitive to the overall size of the cell.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…We have previously demonstrated that waveforms of US signals backscattered from individual biological cells are unaffected by cell nuclei since they are acoustically homogeneous at UHFs. 34 Indeed, the presence of a strongly scattering object within the cell would result in either one or two additional peaks in the time-domain signal depending on the size of the nucleus; however, such peaks were not observed in our experiments. While the US measurements are unaffected by the presence of the cell nucleus, the PA measurements are insensitive to the overall size of the cell.…”
Section: Discussionmentioning
confidence: 53%
“…We demonstrate that, while there were slight differences in the overall size of the cells predicted by the two techniques, good agreement between the two techniques was observed, especially for the calculated N:C ratio values. We have recently reported on an acoustic flow cytometer that sized cell diameter using only US methods 34 and have since incorporated a pulsed laser into our system to enable differentiation of RBCs and white blood cells via simultaneous US/PA detection. 43 Going forward, we plan on translating the presently reported N:C assessment technique to this high-throughput US/PA device to enable largescale investigations of cell population statistics, as well as the detection of cancer cells spiked into a blood sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations